A LLC resonant converter with dual resonant frequency for high light load efficiency. Issue 12 (2nd December 2017) - Qian, Qinsong; Yu, Juzheng; Su, Chang; Sun, Weifeng; Lu, Shengli
ABSTRACT: This paper presents a new approach to achieve high light-load efficiency for inductor-inductor-capacitor ( LLC ) resonant converters. Compared with the conventional LLC resonant converters, an additional active resonant network is employed to give the proposed converter another resonant frequency and another steady state. Thereby, the proposed converter has advantages of narrow switching frequency range and high light-load efficiency. The operation principle and the resonant network switching strategy of the proposed converter are analysed, as well as the design considerations. A 1.2-kW prototype with silicon carbide ( SiC ) MOSFETs is built to verify the proposed converter. The peak efficiency is tested as 94.4% at 680 kHz. Especially, the light-load efficiency is improved from 89% to 91%.